Assessing Geographic Literacy among Form Four Students in Malaysian Secondary Schools - Dziauddin, Mohd Faris (GEOGRAFI, 2017)
This paper reports the empirical findings of a study aimed at investigating the links between geographic literacy and formal education among form four students in Malaysian secondary schools. A quantitative research method was employed using a set of questionnaires with multiple-choice questions designed to test the respondents’ geographic literacy in three domains; knowledge, skill and value. The respondents were 1,031 Form Four students’ aged 16 in national schools in Malaysia. Descriptive and inferential statistics were used to identify the link between literacy level and variables such as gender and school location. The study found that the geographic literacy among form four students in Malaysian secondary schools is at a moderate level (55%). No gender differences were noted, however, school location (urban or rural) have shown significant differences for 10 out of 36 questions. The findings from this study indicated an urgent need to evaluate current practices of teaching and learning as well as assessment of geography education in Malaysian schools in order to improve geographic literacy of students considering the role of the formal education system in this matter.